Distinguishing the crime specified by Article 200.3 of the Criminal Code of the Russian Federation from related crimes - A.Yu. Terekhov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The legal aspects enabling the distinguishing of the crime specified by Art. 200.3 of the Criminal Code of the Russian Federation from related crimes with similar subjects of encroachment were analyzed. The elements of the crimes under the above-said article, as well as their objective and subjective characteristics and the nature of the related crimes were discussed. The study was performed with the use of comparative, systematic, and terminological analysis, along with the methods of generalization. Based on the results obtained, the crimes provided by the article under consideration can be reliably differentiated from the related ones, which is extremely important for further development of the theoretical background of research on crimes in the field of shared construction. The value of the conclusions is obvious for further research on crimes in the field of shared construction, as well as for the subjects of law enforcement activity.